CBX3 regulates efficient RNA processing genome-wide - Smallwood, Andrea; Hon, Gary C.; Jin, Fulai; Henry, Ryan E.; Espinosa, Joaquín M.; Ren, Bing

(untitled) (Genome Research, 2012)
CBX5, CBX1, and CBX3 (HP1α, β, and γ, respectively) play an evolutionarily conserved role in the formation and maintenance of heterochromatin. In addition, CBX5, CBX1, and CBX3 may also participate in transcriptional regulation of genes. Recently, CBX3 binding to the bodies of a subset of genes has been observed in human and murine cells. However, the generality of this phenomenon and the role CBX3 may play in this context are unknown. Genome-wide localization analysis reveals CBX3 binding at genic regions, which strongly correlates with gene activity across multiple cell types. Depletion of CBX3 resulted in down-regulation of a subset of target genes. Loss of CBX3 binding leads to a more dramatic accumulation of unspliced nascent transcripts. In addition, we observed defective recruitment of splicing factors, including SNRNP70, to CBX3 target genes. Collectively, our data suggest a role for CBX3 in aiding in efficient cotranscriptional RNA processing.